2014
DOI: 10.1007/s10551-014-2322-5
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Climate Change and Impression Management: A Case Study Among Canada’s Large Industrial Emitters

Abstract: This paper explores the justifications and impression management strategies that industrial companies use to rationalize their impacts on climate change. These strategies influence the perceptions of stakeholders through the use of techniques of neutralization intended to legitimize the impacts of corporate operations in the area of climate change. Based on a qualitative and inductive approach, 10 case studies were conducted of large Canadian industrial emitters. Interviews were conducted with managers and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 102 publications
6
119
0
4
Order By: Relevance
“…The techniques of neutralization have been analyzed in research on the justification of unethical behaviors by marketing professionals (Vitell and Grove 1987), rationalization of ethical issues inside tobacco companies (Fooks et al 2012), or crisis communication and image repair discourse (Benoit and Czerwinski 1997). More recently, in their case study on the strategies for climate change and impression management tactics, Talbot and Boiral (2014) have identified various neutralization techniques used by large industrial emitters to rationalize their impacts, such as self-proclaimed excellence, denial and minimization, denouncing unfair treatment and deceptive appearances, or economic and technological blackmail.…”
Section: Reporting On Biodiversity or Managing Impressions?mentioning
confidence: 99%
See 1 more Smart Citation
“…The techniques of neutralization have been analyzed in research on the justification of unethical behaviors by marketing professionals (Vitell and Grove 1987), rationalization of ethical issues inside tobacco companies (Fooks et al 2012), or crisis communication and image repair discourse (Benoit and Czerwinski 1997). More recently, in their case study on the strategies for climate change and impression management tactics, Talbot and Boiral (2014) have identified various neutralization techniques used by large industrial emitters to rationalize their impacts, such as self-proclaimed excellence, denial and minimization, denouncing unfair treatment and deceptive appearances, or economic and technological blackmail.…”
Section: Reporting On Biodiversity or Managing Impressions?mentioning
confidence: 99%
“…Most of this literature has focused on the individual level (Bolino et al 2008;Lim 2002). With a few exceptions Bansal and Kistruck 2006;Bansal and Clelland 2004;Talbot and Boiral 2014), this approach has not been used to analyze the manner in which organizations legitimize their contribution to sustainability. As a result, although many studies have criticized organizations' symbolic commitment to sustainability, their focus on image improvement, and the emphasis on a positive rhetoric (Laufer 2003;Cho et al 2010;Unerman et al 2007;Gray 2010;Boiral 2007;Springett 2003), they have overlooked the manner in which negative impacts are rationalized and explained to stakeholders.…”
Section: Contributions To the Literaturementioning
confidence: 99%
“…The fourth objective, legitimation, summarizes activities aimed at retaining or gaining legitimacy for doing the respective business. While some of these measures can be of a rather symbolic nature, others relate to compliance issues, political influence and transparency (Boiral, 2006;Talbot and Boiral, 2015).…”
Section: Research Framework For Corporate Climate Change Strategiesmentioning
confidence: 99%
“…Previous research also showed that these narratives can become even more extensive and cognitively more complex if companies face negative organisational outcomes or allegations which cause them to take refuge in retrospective sense-making . Moreover, Boiral (2016) found that when companies face stakeholder claims regarding socially sensitive issues, they may legitimize their impacts through the use of various rhetoric techniques of neutralization (Talbot and Boiral, 2015b). This is in particular the case if the issue at hand may be seen as non-measurable and potentially unaccountable, such as the specific impacts of mining companies on biodiversity (cf.…”
Section: Identifying the Transparency Fallacymentioning
confidence: 99%